Tatak Pilipino [episode no. 71]. ([Quezon City ABS-CBN, 1992)
A unique display of Pilipino ways and style.
Historical rap calendar events of May (5 min.) -- Beauty contest (20 min.) -- Mga lalaking may bigote (10 min.) -- Aswang, mangkukulam, manananggal and vampira (10 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Beauty contests -- Philippines; Vampires; Witchcraft -- Philippines; Beard; Philippines -- History